Pendekatan Manajemen Risiko dalam Penerapan Higiene Industri dan K3 pada Lingkungan Kerja - Annisa Dwi Sandy; Febby Maharani; Sarah Adelia Hasibuan; Abdurrozzaq Hasibuan (STIKES Columbia Asia Medan, 2026)
Industrial hygiene is a branch of public health research that aims to prevent illness and promote Industrial hygiene is an aspect of public health that prioritizes health protection measures for workers through the identification, evaluation, and control of various elements of the work environment that can cause health problems. The goal of implementing industrial hygiene is to prevent work-related illnesses and create a safe, healthy work environment that supports workers’ well-being. Industrial Safety and Health (IS&H) encompasses these various components, including risk identification, risk assessment, risk mitigation, and worker health monitoring, waste management, and emergency response planning. Workplace risks can include physical, chemical, biological, psychological, and ergonomic hazards. Hazard analysis is a crucial step in industrial hygiene as it helps identify and document potential health risks in the workplace. The hazard analysis process includes hazard identification, risk assessment, hazard prioritization, and risk control. The implementation of Occupational Safety and Health aims to ensure the protection of employees’ safety and health from potential hazards arising from work, while ensuring a safe and sustainable work environment. The implementation of OSH and environmental health also provides broad strategic benefits such as worker protection, cost efficiency, increased productivity, regulatory compliance, and enhanced corporate reputation.